DAMPAK LINGKUNGAN DAN SOSIAL PENGEMBANGAN PARIWISATA DI DESA WISATA PULESARI JOGYAKARTA - Sheva Aulia; Gagih Pradini (Jurnal Ilmiah Hospitality, 2022)
Pulesari tourism village located near mount merapi, located in the Turi subdistrict, Sleman regency, Jogyakarta. Having a river flow that comes from springs and also barking plantations makes Pulesari tourism village as ecotourism and agrotourism. Where one of the activities carried out in the Pulesari village are : Tracking rivers and cultivating salak gardens, besides that the people of Pulesari village usually make the pavilion a gathering place when holding traditional ceremonies. The purpose of this research is to identify the impact of tourism development and activities in Pulesari village. In this study, the data analysis technique used was qualitative where the research carried out observation, interviews and SWOT analysis.